Overview Of Services And Perceptions Of Crossing Service Users At Dumai - Cape Ship Track In Riau Province - Purboyo Purboyo; Sri Kartini; Dewita Lestari (IWJ : Inland Waterways Journal, 2022)
Crossing transportation is one of the transportation media connecting areas that cannot be reached by land routes, because there is no adequate land route to pass.Adequate facilities and infrastructure will be able to facilitate the flow of goods and services as well as human mobility. One of them is the ferry transportation that connects Kota Dumai and Regency Bengkalis (Rupat). The aims of this study were to determine whether the transportation service above KMP. Mountain Muria and KMP. Swarna Dharma has complied with the applicable regulations, how is the perception and satisfaction of service users towards passenger service at KMP. Mountain Muria and KMP. Swarna Dharma as well as knowing what efforts must be made to improve transportation services in accordance with applicable regulations. The data was obtained by observing and identifying problems, using primary and secondary data approaches, primary data in the form of observation and calculation methods, while secondary data in the form of literary and institutional methods. In analyzing the data used validity and reliability test analysis using SPSS 24, analysis of the number of research samples and analysis using the Importance Performance Analysis method. The results obtained in this study KMP. Mountain Muria and KMP. Swarna Dharma has not been able to meet the minimum service standards to service users with applicable regulations.